Assessment of biochemical bone markers of osteoporosis in children with thalassemia major - Tanju Çelik; Özlem Sangün; Şule Ünal; Ali Balcı; Sedat Motor (Italian Journal of Pediatrics, 2022)
Abstract Background Beta thalassemia major (β-TM) is a common cause of skeletal morbidity and is associated with increased bone fracture risk, particularly in inadequately transfused children. The aim of this study was to investigate some potential biochemical markers as possible early predictors of BMD variations in children with β-TM. Methods The study included 38 children with β-TM and 40 sex-age matched controls. All patients were subjected to BMD assessment by dual-energy X-ray absorptiometry (DEXA). Serum beta-crosslaps (beta-CTx), osteoprotegerin (OPG), receptor activator of nuclear factor-kappa B ligand (RANKL), urinary deoxypyridinoline (DPD) and ferritin levels were compared between the groups. Results Serum OPG levels were significantly lower in thalassemic children than in controls. The mean ratio of RANKL/OPG was significantly higher in the thalassemic patients than in the control group. Osteoporosis was detected in 10 (3 female and 7 male) of 38 patients (26.3%) according to the femur Z score and in 6 of them (4 male and 2 female) (15.8%) according to the spine Z score. Conclusions Serum OPG concentrations can be used as a biochemical marker in screening patients with beta-thalassemia major for the development of osteoporosis.